Increases in vein length compensate for leaf area lost to lobing in grapevine. Issue 7 (19th July 2022) - Migicovsky, Zoë; Swift, Joel F.; Helget, Zachary; Klein, Laura L.; Ly, Anh; Maimaitiyiming, Matthew; Woodhouse, Karoline; Fennell, Anne; Kwasniewski, Misha; Miller, Allison J.; Cousins, Peter; Chitwood, Daniel H.
Abstract: Premise: Leaf lobing and leaf size vary considerably across and within species, including among grapevines ( Vitis spp.), some of the best‐studied leaves. We examined the relationship between leaf lobing and leaf area across grapevine populations that varied in extent of leaf lobing. Methods: We used homologous landmarking techniques to measure 2632 leaves across 2 years in 476 unique, genetically distinct grapevines from five biparental crosses that vary primarily in the extent of lobing. We determined to what extent leaf area explained variation in lobing, vein length, and vein to blade ratio. Results: Although lobing was the primary source of variation in shape across the leaves we measured, leaf area varied only slightly as a function of lobing. Rather, leaf area increases as a function of total major vein length, total branching vein length, and vein to blade ratio. These relationships are stronger for more highly lobed leaves, with the residuals for each model differing as a function of distal lobing. Conclusions: For leaves with different extents of lobing but the same area, the more highly lobed leaves have longer veins and higher vein to blade ratios, allowing them to maintain similar leaf areas despite increased lobing. These findings show how more highly lobed leaves may compensate for what would otherwise result in a reduced leaf area, allowing for increased photosynthetic capacity through similar leaf size.